A mouse model of lung cancer induced via intranasal injection for anticancer drug screening and evaluation of pathology. Issue 1 (29th November 2022) - Tanaka, Ryo; Yoshinouchi, Shosei; Karouji, Kento; Tanaka, Yuki; Tominari, Tsukasa; Hirata, Michiko; Matsumoto, Chiho; Itoh, Yoshifumi; Miyaura, Chisato; Inada, Masaki
Abstract : The pathologies and lethality of lung cancers are associated with smoking, lifestyle, and genomic factors. Several experimental mouse models of lung cancer, including those induced via intrapulmonary injection and intratracheal injection, have been reported for evaluating the pharmacological effect of drugs. However, these models are not sufficient for evaluating the efficacy of drugs during screening, as these direct injection models ignore the native processes of cancer progression in vivo, resulting in the inadequate pathological formation of lung cancer. In the present study, we developed a novel intranasal injection model of lung cancer simulating the native lung cancer pathology for anticancer drug screening. A mouse lung cancer cell line (Lewis lung carcinoma; LCC) was intranasally injected into mouse lungs, and injected cell number‐dependent cancer proliferation was apparent in both the left and right lungs. Human non‐small‐cell lung cancer (NCI‐H460) cells were also intranasally injected into nude mice and similarly showed injected cell number‐dependent cancer growth. For the pharmacological evaluation of cisplatin, two different treatment frequencies were tested four times per month and twice a month. The intranasal injection model confirmed that cisplatin suppressed lung cancer progression to a greater extent under the more frequent treatment condition. In conclusion, these results indicated that our intranasal injection model is a powerful tool for investigating lung cancer pathology and may aid in the development of new anti‐lung cancer agents. Abstract : We developed new mouse models of mouse and human lung cancers that were stably induced by intranasal injection. The intranasal injection model confirmed that cisplatin suppressed lung cancer progression, thus validating that this technique could be useful in investigating lung cancer pathologies and therapeutic agents.